Preliminary Diagnostic Assessment in Distance Learning at SMAN 1 Pagaden - Mimih Sukmayanti; Hani Chaerunnisa; Anwar Shidiq Santoso (Edunesia: Jurnal Ilmiah Pendidikan, 2021)
So far, distance learning still faces many obstacles in its implementation. Starting from compiling lesson plans, learning methods, to conducting evaluations. Moreover, the psychological factors of students in facing this pandemic, they are required to study at home with various kinds of challenges and obstacles. Limitations of gadgets (smartphone), internet quota to internet networks that do not reach where they live because they are in rural areas. To find a solution to this problem, a study was conducted regarding the initial conditions of SMAN 1 Pagaden students in carrying out this distance learning. By using the Miles & Huberman analysis method, which will find interactive patterns of relationships and to get an understanding of the meaning of the obstacles faced in the distance learning process at SMAN 1 Pagaden by using non-verbal interview techniques. The questionnaire is distributed via google form which then the data obtained is used as a reference for developing distance learning strategies. Based on the results of interviews, based on respondents who answered that distance learning at SMAN 1 Pagaden was less effective, it was 49.8%. Students hope that distance learning does not give many assignments but there is material delivery through google meet or zoom meeting. For students who are not reached by internet and gadget (smartphone) facilities, the visiting teacher model is carried out with small groups.